Challenges in Surveillance for Streptococcal Toxic Shock Syndrome (STSS): Active Bacterial Core Surveillance (ABCs) - Hani jafaar Bumejdad et al. (International Journal of Scientific Research and Innovative Studies, 2024)
Streptococcal toxic shock syndrome (STSS) is a rare but severe condition caused by invasive infections with group A Streptococcus (GAS). The Active Bacterial Core Surveillance (ABCs) system plays a crucial role in monitoring the epidemiology of STSS, but challenges remain in accurately capturing cases and identifying risk factors(1,2). This review outlines the obstacles in STSS surveillance, including diagnostic difficulties, underreporting, and variations in clinical presentations. It also discusses strategies to address these challenges, such as enhanced data collection, education initiatives, and technological advancements. Received Date: July 08, 2024 Accepted Date: July 29, 2024 Published Date: August 01, 2024 Available Online at: https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/307 DOI: https://doi.org/10.5281/zenodo.14647810